Free triiodothyronine to free thyroxine ratio as a marker of poor prognosis in euthyroid patients with acute coronary syndrome and diabetes after percutaneous coronary intervention - Wang, Shen; Wang, Yue; Sun, Shuaifeng; Li, Fadong; Zhao, Wenxin; Li, Xinjian; Ye, Maomao; Niu, Yufei; Wu, Xiaofan (Frontiers in Endocrinology, 2024)
Abstract Objectives: In recent years, the free triiodothyronine/free thyroxine (FT3/FT4) ratio, a new comprehensive index for evaluating thyroid function, which could reflect thyroid function more stably and truly than serum thyroid hormone level, has been demonstrated to correlate with the risks of diabetes and cardiovascular disease in euthyroid adults. However, the correlation between thyroid hormone sensitivity and long-term prognosis in euthyroid patients with acute coronary syndrome (ACS) and diabetes after percutaneous coronary intervention (PCI) remains unclear. Methods: A total of 1786 euthyroid patients with ACS who successfully underwent PCI at Beijing Anzhen Hospital from August 2021 to April 2022 were included in our study, which was divided into three groups according to tertiles of thyroid hormone sensitivity index. Cox regression, Kaplan-Meier, and receiver-operating characteristic analyses were applied to analyze the associations between the FT3/FT4 ratio with ACS and diabetes after PCI. Results: Our analysis indicated that a lower level of FT3/FT4 ratio in euthyroid patients with acute coronary syndrome (ACS) and diabetes after PCI showed significantly higher incidences of MACCE when compared with a higher level of FT3/FT4 ratio. After adjusting for other covariates, patients with a lower level of FT3/FT4 ratio were negatively associated with the risk of MACCE than those with a higher level of FT3/FT4 ratio (adjusted OR =1.61,95% CI 1.05–2.47, P=0.028). In subgroup analyses, individuals were stratified by age, sex, BMI, ACS type, hypertension, and dyslipidemia, showing that there were no significant interactions between the FT3/FT4 ratio and all subgroups for MACCE. In addition, the FT3/FT4 ratio performed better on ROC analyses for cardiac death prediction (area under the curve (AUC) 0.738). Conclusion: Reduced level of FT3/FT4 ratio was a potential marker of poor prognosis in euthyroid patients with ACS and diabetes after PCI. Keywords: FT3/FT4 ratio, Prognosis, Acute coronary syndrome, Percutaneous coronary intervention, Diabetes